2016
DOI: 10.1039/c5md00459d
|View full text |Cite
|
Sign up to set email alerts
|

Rubrolide analogues and their derived lactams as potential anticancer agents

Abstract: Analogues of rubrolides were synthesized and shown to be cytotoxic to several cancer cell lines and not toxic to L929 normal cells. The cytotoxicity involved the induction of cell death by apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
1
12
0
2
Order By: Relevance
“…RMN de 1 H (300 MHz, CDCl 3 ) δ 3,84 (s, 3H, 7'), 3,88 (s, 3H, 7''), 6,92 (d, J 3',2' = J 5',6' = 8,4 Hz, 2H, 3' e 5'), 6,97 (d, J 3'',2'' = J 5'',6'' = 8,5 Hz, 2H, 3'' e 5''), 7,62 (d, J 2',3' = J 6',5' = 8,4 Hz, 2H, 2' e 6'), 8,18 (d, J 2'',3'' = J 6'',5'' = 8,5 Hz, 2H, 2'' e 6''). RMN de 13 C (75 MHz, CDCl 3 ) δ 55,5 (7'), 55,6 (7''), 86,8 (2), 93,5 (1), 112,1 (1'), 113,8 (3'' e 5''), 114,4 (3' e 5'), 130,4 (1''), 131,9 (2'' e 6''), 135,0 (2' e 6'), 161,5 (4'), 164,3 (4''), 176,8 (3) 14), 239 (12), 238 (71), 224 (16), 223 (100), 195 (28), 180 (12), 163 (7), 160 (7), 159 (71), 152 (29), 151 (10), 144 (18), 135 (20), 131 (6), 126 (7), 119 (35), 116 (23), 107 (7), 92 (24), 88 (21), 87 (8), 77 (43), 76 (11), 75 (13), 74 (11), 64 (24), 63 (36), 62 (23), 51 (15), 50 (14).…”
Section: -(3-bromo-4-metoxifenil)-1-(35-dibromo-4-metoxifenil)prop-mentioning
confidence: 99%
See 3 more Smart Citations
“…RMN de 1 H (300 MHz, CDCl 3 ) δ 3,84 (s, 3H, 7'), 3,88 (s, 3H, 7''), 6,92 (d, J 3',2' = J 5',6' = 8,4 Hz, 2H, 3' e 5'), 6,97 (d, J 3'',2'' = J 5'',6'' = 8,5 Hz, 2H, 3'' e 5''), 7,62 (d, J 2',3' = J 6',5' = 8,4 Hz, 2H, 2' e 6'), 8,18 (d, J 2'',3'' = J 6'',5'' = 8,5 Hz, 2H, 2'' e 6''). RMN de 13 C (75 MHz, CDCl 3 ) δ 55,5 (7'), 55,6 (7''), 86,8 (2), 93,5 (1), 112,1 (1'), 113,8 (3'' e 5''), 114,4 (3' e 5'), 130,4 (1''), 131,9 (2'' e 6''), 135,0 (2' e 6'), 161,5 (4'), 164,3 (4''), 176,8 (3) 14), 239 (12), 238 (71), 224 (16), 223 (100), 195 (28), 180 (12), 163 (7), 160 (7), 159 (71), 152 (29), 151 (10), 144 (18), 135 (20), 131 (6), 126 (7), 119 (35), 116 (23), 107 (7), 92 (24), 88 (21), 87 (8), 77 (43), 76 (11), 75 (13), 74 (11), 64 (24), 63 (36), 62 (23), 51 (15), 50 (14).…”
Section: -(3-bromo-4-metoxifenil)-1-(35-dibromo-4-metoxifenil)prop-mentioning
confidence: 99%
“…35 e anteriormente empregadas com sucesso para o preparo de vários análogos de nostoclídeos [36][37][38][39] e rubrolídeos. [19][20][21][22][23][24] Para isso, as lactonas foram submetidas à reação com os aldeídos na presença de TBDMSOTf e DIPEA. Esse procedimento resulta na formação de um sililfurano intermediário que condensa com o aldeído resultando na formação de um sililéter intermediário.…”
Section: Sínteseunclassified
See 2 more Smart Citations
“…In 2016, Barbosa and coworkers found that compound 91n caused a decrease in HL-60 cell viability followed by an increase in the apoptoric and necrotic cells in a concentration dependent manner [179].…”
Section: Scheme 92 Synthesis Of (Z)-5-(1-arylmethylene)-3bromo-4-(5-mentioning
confidence: 99%